2021
DOI: 10.1186/s40168-021-01054-5
|View full text |Cite|
|
Sign up to set email alerts
|

A multi-OMIC characterisation of biodegradation and microbial community succession within the PET plastisphere

Abstract: Background Plastics now pollute marine environments across the globe. On entering these environments, plastics are rapidly colonised by a diverse community of microorganisms termed the plastisphere. Members of the plastisphere have a myriad of diverse functions typically found in any biofilm but, additionally, a number of marine plastisphere studies have claimed the presence of plastic-biodegrading organisms, although with little mechanistic verification. Here, we obtained a microbial community… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(46 citation statements)
references
References 111 publications
1
45
0
Order By: Relevance
“…BHET2 and Bacillus sp. BHET2 and the presence of PET hydrolytic intermediates confirmed their degradation ability (Wright et al, 2021). The exploration of microbial communities through metagenomics could serve as a great tool for mining novel enzymes and genes involved Fig.…”
Section: Relevance Of Microbes In Plastic Degradationmentioning
confidence: 79%
“…BHET2 and Bacillus sp. BHET2 and the presence of PET hydrolytic intermediates confirmed their degradation ability (Wright et al, 2021). The exploration of microbial communities through metagenomics could serve as a great tool for mining novel enzymes and genes involved Fig.…”
Section: Relevance Of Microbes In Plastic Degradationmentioning
confidence: 79%
“…Specifically, Idiomarina has been recently reported to possibly assist in the formation of biofilms on the surface of PET particles, although it showed no significant PET degradation (Gao & Sun, 2021). On the contrary, although there is no previous report on the ability of Bacillus algicola (which showed double CFU count when incubated with PET) to degrade plastic polymers, other species and strains within the genus have been described as degraders of polystyrene, polypropylene, polyethylene, and PET microplastic particles (Auta et al, 2017; Wright, Bosch, et al, 2021) as well as polyvinyl chloride (Giacomucci et al, 2019). Finally, the yeast Rhodotorula evergladensis , which showed a tiny increase in growth on PET in our study, has been previously reported to degrade plasticizers (Gartshore et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Microplastic serves as an excellent substratum for biofilm attachment as they adsorb essential nutrients and organic matter from the surrounding environment to support microbial growth. Usually, the microbes colonize the plastics within 24 h [179] depending on several environmental factors, which significantly influence the microbial composition of the plastisphere [74]. The fluorescence microscopy (FM) and scanning electron microscopy (SEM) recognize the microbial association in the biofilm [47,89,92,206,207] (Table 3).…”
Section: Characterization Technologiesmentioning
confidence: 99%